Adolescents' ratings of features of parks that encourage park visitation and physical activity. Issue 1 (December 2016) - Veitch, Jenny; Salmon, Jo; Parker, Kate; Bangay, Shaun; Deforche, Benedicte; Timperio, Anna
Abstract Background The neighbourhood environment such as the availability of parks are a key, but under-researched, influence on adolescents' physical activity. In addition to overall physical activity levels, park-based physical activity and park visitation is low in this age group. Thus, it is critical to identify park features that may encourage or discourage adolescents from visiting parks. This study used a novel methodology to identify key physical characteristics of parks that are perceived to be important for park visitation and park-based physical activity among adolescents. Methods Four secondary schools located in low, mid and high socio-economic status areas of Victoria, Australia were recruited. Using a purpose-built computer application, students in years 8–10 were presented with 44 original photographic images of park features. Participants rated each image (range 1–10) on how likely the feature would be to encourage them to visit a park and to engage in park-based physical activity, and placed symbols ('thumbs up'/'thumbs down') on aspects of the image that had a positive or negative influence on their ratings. Results Participants (n  = 99) had a mean age of 13.3 years (SD = 0.87) and 53 % were female. Overall, the top three rated images prompting park visitation by adolescents were: a long steep slide, a flying fox and a table tennis table. These first two features were also reported as being likely to promote physical activity in the park. Differences in ratings were observed for boys and girls. The images that received the greatest number of "thumbs-up" symbols included large swings and slides, table tennis tables, no-smoking signs, flying foxes and BMX tracks. The images that received the greatest number of "thumbs-down" symbols included signage about rules, graffiti, toilets, concrete steps, and skate bowls. Conclusion Physically challenging play equipment is likely to encourage adolescents to visit and be active in parks. Rules, graffiti, toilets and skate bowls may discourage visitation. It is important for park designers, planners and policy makers to consider adolescents' views of what park design features are important so that parks are created that support and encourage visitation and optimise levels of physical activity when in the park.